An Evaluation of Barriers obstructing the Applicability of Public Private Partnership (PPP) in Infrastructure Development - Sedqi Esmaeel Rezouki; Jinan Kata'a Hassan (Civil Engineering Journal, 2019)
Shortage in funds after the declining in oil prices since 2014, made Iraq government encourage private sector engagement in financing infrastructure projects through PPP. However, private sector reluctance was notable.  Therefore, this research is conducted to assess if Iraq is a supportive environment for PPP projects development. 25 risk factors of PPP projects have been listed and organized within a questionnaire that was conducted with a participation of 98 respondents from public, private institutions and academics. Means comparison was used to rank and identify respondent agreement on assessing the level of importance of these risk factors, also nonparametric tests were used. Findings indicated that all respondents groups have agreed on ranking corruption on the top of barriers that government should deal with to ensure the success of PPP projects. Afterward scarcity of private funds came in the first place followed by insufficient public administration processes and then by the lack of legal framework followed by the delays in acquisition of land and while the lack of sovereign guarantee came at the fifth place. The perceptions of survey groups’ respondents concerning the importance of risk factors differ , where both public and academics respondents have serious concerns regarding the private sector capacity to carry out the task and the availability of private funds. On the other hand the private sector concerns the availability of government incentives to support for infrastructure PPP projects. Overall findings indicated that government must work on building a solid enabling environment before the initiation of PPP approach in Iraq.